Disfunção endotelial em pacientes com Sindrome Nefrótica Idiopática e sua correlação com marcadores de lesão do glicocálix - Salmito, Francisco Thiago Santos (2015)
ABSTRACT Introduction : The kidneys are organs of the urinary system, it is the main organ that makes up the excretory system and osmoregulator responsible for sift through waste in the blood and excrete them with water. Glomerular diseases are the result of a wide variety of factors: immune disorders, vascular diseases, metabolic disorders, and some inherited entities. Nephrotic syndrome (NS) is characterized by the presence of massive proteinuria, edema, hypoproteinemia and dyslipidemia, is associated wit h increased risk of coronary morbidity and mortality. The endothelial dysfunction is described as an early stage of atherosclerosis resulting disturbances in the physiology of several vasoactive molecules. Objective : To evaluate endothelial dysfunction in patients with idiopathic nephrotic syndrome and its correlation with glycocalyx injury markers. Methods: Cross - sectional study in patients with a confirmed diagnosis of idiopathic nephrotic syndrome, from January to August 2014. Resultados: Of the 49 patient s with NS, 25 (51.0%) were female. The average age of - hour urinary protein was in the range of 5.5 nephrotic 2.4 g / 24 h and decreased serum albumin at 2.7 8.6 g / dl. The average glomerular filtratio n rate was 72.3 23.4 mL / min / 1.73m2. Among the results of the kidney biopsy, the diagnosis of glomerulopathies, showed greater focal segmental glomerulosclerosis presence / minimal injury (40.81%). Thirty - five patients were being treated with ACE inhibi tors or antagonist of the angiotensin II receptor. No patient had started immunosuppressive therapy. Thirty - two patients had clinically detectable peripheral edema. After adjusting for age and glomerular filtration rate, syndecan - 1 was significantly associ ated with 24 - hour urinary protein excretion, LDL cholesterol, HDL cholesterol and triglycerides. ICAM - 1 was associated only with the serum total cholesterol, whereas E - selectin was associated with LDL cholesterol. FMD was associated with total serum choles terol and LDL cholesterol. Discussion : In this study, it was first demonstrated that patients with SN significance of damage to the endothelial glycocalyx, as demonstrated by elevated levels of syndecan - 1. In addition, the endothelial glycocalyx damage are associated with many biochemical features SN (urinary protein excretion 24 hours, LDL cholesterol, HDL cholesterol and triglycerides) and appears to be a link between endothelial dysfunction and nephrotic syndrome in these patients